Ketahanan Remaja di Panti Asuhan - Ni Komang Krisnawati Mangna; Tience Debora Valentina (Humanitas (Jurnal Psikologi), 2024)
Adolescents who live in orphanages need to have resilience skills to help them recover from adversity that triggers psychological stress while living in an orphanage. This research aims to determine the factors that influence resilience in adolescents living in orphanages. The method used in this paper is a literature review. Article search sources were accessed from Google Scholar library sources with article publication years between 2014-2023. The results of this literature review are internal factors (emotional intelligence, self-compassion, self-disclosure, self-esteem and self-acceptance) and external factors (social support in the form of emotional support from caregivers and peers) that influence resilience abilities in adolescent orphanages.